Spectrum, progression and predictors of morbidity in perinatally HIV-infected adolescents on antiretroviral therapy - Frigati, Lisa Jane (Department of Paediatrics and Child Health, 2021)
Background: Long term survival of children living with HIV due to improved early access to antiretroviral therapy (ART) is contributing to a growing population of adolescents living with perinatally acquired HIV (PHIV+) at risk of developing chronic multisystem comorbidity. There is limited knowledge on the overall burden, progression and causes of morbidity in PHIV+ adolescents, especially in resource limited settings. Much of what is known about morbidity in PHIV+ adolescents relates to single organ system pathology and there is a lack of a holistic approach to PHIV+ adolescents and their overall health. The aim of this PhD project was therefore to investigate the spectrum and determinants of chronic morbidity, the progression of disease and intercurrent illness in PHIV+ adolescents on ART over a 4- year period. Methods: This was a prospective study of participants enrolled in the Cape Town Adolescent Antiretroviral Cohort (CTAAC), a longitudinal cohort study, that recruited 515 PHIV+ adolescents and 110 HIV negative (HIV-) adolescents matched by age from 7 health care sites in Cape Town, South Africa. Eligibility criteria included PHIV+ adolescents who were aged 9-14 years, who had been on ART for at least 6 months and were aware of their HIV status. All adolescents and caregivers gave informed consent/assent. Participants were followed 6-monthly with questionnaires, clinical examination with detailed pulmonary (lung function), neurocognitive (magnetic resonance imaging and a battery of neurocognitive tests), cardiovascular (echocardiogram and ECG) and laboratory investigations. Analyses for each specific objective of the PhD were developed. Three analyses used data from the enrolment visit and were primarily descriptive and two were longitudinal and examined the incidence of hospitalizations, QuantiFERON conversion (an interferon gamma release assay used to measure Mycobacterium tuberculosis infection) and Tuberculosis (TB) disease. Results: Five hundred fifteen PHIV+ and 109 HIV- participants had a median follow-up of 4.1 years (IQR: 3.7–4.6). At enrollment, PHIV+ adolescents had a median duration of ART of 7.6 years (IQR: 4.6–9.2), median CD4 count of 713 cells/mm3 (IQR: 561.0–957.5) and 387 (75%) had a viral load of <50 copies/mL. Neurocognitive impairment was present in more than half of the PHIV+ cohort (56.3% vs. 45.3% in HIV-, p=0.05) but renal impairment was rare (2.3% in PHIV+ vs. 2.1% in HIV-, p=0.89). Microalbuminuria was also rare (8.0 in PHIV+ vs. 9.0% in HIV-, p=0.80). Respiratory or cardiac impairment were more common in PHIV+ adolescents than in HIV- participants (27.1% vs. 14.7%, p=0.01 and 46.1% vs. 33.7%, p=0.03, respectively). Multisystem impairment (defined as impairment of ≥ 3 systems) was uncommon, with only 10% of PHIV+ adolescents having 4-system impairment. Metabolic abnormalities, such as insulin resistance (IR), were relatively common but IR rates did not differ compared to HIV- adolescents (18 vs. 20%, p= 0.17). Incidence rates for hospitalization were 6.6 per 100-person-years (PY) in PHIV+ adolescents, three times that of HIV- adolescents. Sixty percent of hospitalization episodes were due to non-infectious causes and 24% due to infectious causes, of which pneumonia and TB were the predominant causes. PHIV+ adolescents had a substantially higher incidence of TB disease than HIV- adolescents (2.2/100 PY, 95% CI 1.6-3.1 vs. 0.3/100 PY, 95% CI 0.04-2.2), despite a similar rate of TB infection, as measured by QuantiFERON positivity. TB disease was associated with low CD4 counts and high viral loads in PHIV+ adolescents. Conclusion: Chronic single system morbidity experienced by PHIV+ adolescents on ART was common and merits further study, as this population begins to engage in adult lifestyle factors, such as smoking and alcohol use, that may compound these abnormalities. However, multisystem morbidity was relatively rare. In addition, in a relatively small percentage of adolescents there were subclinical metabolic abnormalities (IR and microalbuminuria) that may result in increased morbidity especially with regards to diabetes and cardiovascular disease in later life. The high burden of hospitalization and intercurrent disease, mainly due to TB, could be prevented by proven strategies, such as TB preventive therapy and ensuring adherence to optimal ART regimens.